Assessment of Patient Safety Culture among Nurses at a Tertiary Level Hospital in Kathmandu - Sabitra Poudel; Menuka Aryal; Narayani Paudel (Journal of Karnali Academy of Health Sciences, 2019)
Introduction: Patient safety is a fundamental and critical dimension of quality health care. Globally it is becoming a major challenge in achieving universal health coverage. The challenge is even more serious in Low and Middle-Income Countries like Nepal because safety-related harm is more in these countries rather than in developed countries. This study aims to assess patient safety culture among nurses.